2021
DOI: 10.2147/ott.s300480
|View full text |Cite
|
Sign up to set email alerts
|

RPN2 Predicts Poor Prognosis and Promotes Bladder Cancer Growth and Metastasis via the PI3K-Akt Pathway

Abstract: Background Ribophorin II (RPN2) is a highly conserved glycoprotein involved in the N-linked glycosylation of multiple proteins. RPN2 was reported to be associated with malignant phenotype in several tumors. However, the function of RPN2 in bladder cancer (BCa) remains unclear. Methods Expression of RPN2 in BCa and adjacent tissues was compared by bioinformatics analysis, immunohistochemistry, and Western blotting. qRT-PCR was performed to explore the correlation between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Functional enrichment analysis showed that GBM samples with high expression of both WEE2-AS1 and RPN2 were significantly enriched in the AKT signaling pathway (Figure 4 A-C and Figure S1 ). In addition, PI3K-Akt was a downstream signaling pathway of RPN2 in other tumors articles 24 , 25 . Thus, we then investigated the phosphorylation levels of PI3K and Akt in WEE2-AS1 knockdown and overexpression GBM.…”
Section: Resultsmentioning
confidence: 99%
“…Functional enrichment analysis showed that GBM samples with high expression of both WEE2-AS1 and RPN2 were significantly enriched in the AKT signaling pathway (Figure 4 A-C and Figure S1 ). In addition, PI3K-Akt was a downstream signaling pathway of RPN2 in other tumors articles 24 , 25 . Thus, we then investigated the phosphorylation levels of PI3K and Akt in WEE2-AS1 knockdown and overexpression GBM.…”
Section: Resultsmentioning
confidence: 99%
“…In BLCA, TEAD4 activates the PI3K/AKT pathway, which in turn promotes invasion and metastasis 27 . Knockdown of RPN2 gene has been shown to suppress EMT and inhibit the PI3K/AKT pathway 49 . Additionally, the E3 ubiquitin ligase RNF126 plays a key role in BLCA metastasis by regulating the stability of PTEN, an inhibitor of the PI3K/AKT signaling pathway 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we also identified 11 genes that interacted with HSP90B1 and were highly correlated with HSP90B1: RPN2, SDF2L1, HSPA5, HYOU1, PPIB, GANAB, PDIA6, PDIA4, CALR, TG, and P4HB. RPN2 is speculated to be involved in the progression of malignant tumours by regulating various signalling pathways, such as STAT3, NF-κB, and PI3K-Akt [ 40 , 41 ]. It is also considered a promising prognostic biomarker for colorectal cancer, non-small-cell lung cancer, and gastric adenocarcinoma [ 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%